Medical Supplies Export Controls and Bans During the Early COVID-19 Pandemic in Southeast Asian Countries Compliance with the WTO - Wicaksono, Raden Mas Try Ananto Djoko; Rinaldi, Rina Putri (Universitas Pelita Harapan, 2022)
The global markets for crucial COVID-19 products (medical supplies) are highly concentrated. Most of developing countries are highly dependent on imports for these products. However, majority of countries implemented the export controls and bans on medical supplies due to the limitation of resources they have. This research examines the Southeast Asian policy on medical supplies export controls and bans in response to the COVID-19 Pandemic and its justification for export restrictions based on Article XI paragraph (2), Article XX, and Article XXI GATT 1994. The research methods are based on qualitative methods and normative juridical research methods. This research uses secondary data from journals, books, official documents, and websites related to the Southeast Asian Government policy on export. The results show that the justification for the export ban and restriction on medical equipment can be exempted by referring to Article XX regarding general exceptions and regarding security exceptions in Article XXI (b) (iii). Most of the Southeast Asian countries tried to follow the provisions of GATT 1994 and its reflection to be a good international citizen by compliance the international law.